Cellulose-polyhydroxylated fatty acid ester-based bioplastics with tuning properties: Acylation via a mixed anhydride system. (1st October 2017) - Heredia-Guerrero, José A.; Goldoni, Luca; Benítez, José J.; Davis, Alexander; Ceseracciu, Luca; Cingolani, Roberto; Bayer, Ilker S.; Heinze, Thomas; Koschella, Andreas; Heredia, Antonio; Athanassiou, Athanassia
Highlights: New cellulose esters were synthesized by condensation of cellulose and aleuritic acid. The mechanical behavior was changed from rigid to ductile, keeping the same toughness. These materials show similar properties to commercial cellulose derivatives. Abstract: The synthesis of microcrystalline cellulose (MCC) and 9, 10, 16-hydroxyhexadecanoic (aleuritic) acid ester-based bioplastics was investigated through acylation in a mixed anhydride (trifluoroacetic acid (TFA)/trifluoroacetic acid anhydride (TFAA)), chloroform co-solvent system. The effects of chemical interactions and the molar ratio of aleuritic acid to the anhydroglucose unit (AGU) of cellulose were investigated. The degree of substitution (DS) of new polymers were characterized by two-dimensional solution-state NMR and ranged from 0.51 to 2.60. The chemical analysis by attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR) confirmed the presence of aleuritate groups in the structure induces the formation of new H-bond networks. The tensile analysis and the contact angle measurement confirmed the ductile behavior and the hydrophobicity of the prepared bioplastics. By increasing the aleuritate amounts, the glass transition temperature decreased and the solubility of bioplastic films in most common solvents was improved. Furthermore, this new polymer exhibits similar properties compared to commercial cellulose derivatives.